Gender and Resource Co-Management in Northern Canada - Natcher, David C. (ARCTIC, 2013)
An inventory of the nominal representation of men and women on northern co-management boards in the Yukon, Northwest Territories, and Nunavut identified a total of 34 co-management boards. Of their total of 210 members, 176 (84%) were males and 34 (16%) were females. Nine boards were composed exclusively of men, and 18 boards had only a single female representative. The land and resource management regimes created through the settlement of comprehensive land claims have afforded Aboriginal governments equitable representation in co-management but have not promoted gender equity in board membership. L’inventaire de la représentation nominale d’hommes et de femmes faisant partie de conseils de cogestion dans le Nord, plus précisément au Yukon, dans les Territoires du Nord-Ouest et au Nunavut, a permis de répertorier 34 conseils de cogestion au total. En tout, ces conseils comprenaient 210 membres, dont 176 (84 %) étaient des hommes et 34 (16 %) étaient des femmes. Neuf conseils étaient exclusivement composés d’hommes et 18 conseils ne comptaient qu’une seule femme. Les régimes de gestion des ressources et des terres découlant du règlement d’importantes revendications territoriales ont permis une représentation équitable sur le plan de la cogestion des gouvernements autochtones, mais n’ont pas fait valoir l’équité entre les sexes au sein des conseils de cogestion.